IMPACT PATHWAYS OF COVID-19 ON AGRICULTURE AND GOVERNMENT REFORMS IN INDIA: AN OVERVIEW - Paul Mansingh, J., Nisha, Ravi Kanth Makarla, M (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The COVID-19 pandemic severely influenced all the areas including agriculture. The effect of COVID-19 on agriculture varies from country to country among farmers. In India, small and marginal farmers are worst affected by the first lockdown. As the COVID-19 pandemic is a recent phenomenon, there is a dearth of studies in determining its impacts on farming and the related sectors. Hence, the relevant and recent literature was reviewed and the possible impact felt in farm production, food demand, and the price is organized thematically and the impact pathways are identified. The impact pathway clearly describes the impact on agriculture. Several lessons were learned namely the importance of social programs, institutional credit, input delivery, e-commerce, and storage structures. Many innovative models were also developed and implemented by farmers, Self-Help Groups, Farmer Producer Organizations, and private enterprises in supply chain management. The Government of India has announced relief packages like free ration and cash transfers for the poor and loan moratorium for farmers. To transform the crisis as an opportunity, the government proposed many reforms in the Essential Commodities Act, the Agricultural Products Market Committee Act, and the Contract Farming Act.